2017
DOI: 10.1063/1.4974954
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative photoacoustic characterization of blood clot in blood: A mechanobiological assessment through spectral information

Abstract: Formation of blood clots, called thrombus, can happen due to hyper-coagulation of blood. Thrombi, while moving through blood vessels can impede blood flow, an important criterion for many critical diseases like deep vein thrombosis and heart attacks. Understanding mechanical properties of clot formation is vital for assessment of severity of thrombosis and proper treatment. However, biomechanics of thrombus is less known to clinicians and not very well investigated. Photoacoustic (PA) spectral response, a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…However, the imaging resolution in PACT is limited by the center frequency and bandwidth of the transducer [ 29 ]. Research has revealed that the frequency components of PA signals are related to the sizes and contents of the absorbers [ 30 , 31 ]. PA frequency analysis has been widely applied in examining fatty livers [ 32 ], bones [ 33 ], and blood cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the imaging resolution in PACT is limited by the center frequency and bandwidth of the transducer [ 29 ]. Research has revealed that the frequency components of PA signals are related to the sizes and contents of the absorbers [ 30 , 31 ]. PA frequency analysis has been widely applied in examining fatty livers [ 32 ], bones [ 33 ], and blood cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, PA techniques have been also investigated to study thermal coagulation of tissues based on changes in PA signal amplitudes due to changes in optical properties of tissues during coagulation [32]. However, such PA amplitude-based differentiation is often not reliable because the PA signal strength depends nonlinearly on an input laser energy and a distance between tissue sample and acoustic sensor [15]. In this regard, our proposed PA spectral sensing technique is more robust and predictable as it utilizes the frequency of PA response that is relatively less sensitive to experimental parameters, compared to the case of PA pressure amplitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the proposed technique relies on changes in the elastic property of tissue that serves as a potential fingerprint in coagulated tissue study. Our approach has been previously adopted to diagnose different pathological conditions involving minute changes in elastic properties [15,33]. This exhibits the versatility and sensitivity of our PA spectral sensing technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BEARD, 2009) reflete, a concentração em termos do coeficiente de absorção óptica e as características de microestruturas dos tecidos também podem refletir em mudanças do espectro de frequências acústicas contidas nos sinais FA gerados no tecido de interesse. Por exemplo, durante o tempo de coagulação, a absorção óptica varia à medida que o sangue se transforma em coágulo, podendo ser utilizada para estagio de coágulos (KARPIOUK et al, 2008;BISWAS et al, 2017).…”
Section: Experimentounclassified